Hipotesis dan Uji Hipotesis dalam Bidang Pendidikan - Siti Halimah; M. Duskri (Journal of Innovative and Creativity, 2025)
This research discusses the concept and application of hypotheses and hypothesis testing in the field of education. Hypotheses have an important role in directing the research process, especially in quantitative approaches. However, many novice researchers still do not thoroughly understand how to formulate hypotheses and choose appropriate testing methods, so there are often errors in data interpretation. This research uses a qualitative approach with a literature study method of relevant literature on statistical hypotheses, types of hypotheses, common errors in testing, and their application in educational research. This article emphasizes the importance of understanding how to formulate and test hypotheses appropriately to increase the validity of research results. Examples of application in education are presented to demonstrate the role of hypothesis testing in assessing learning methods and student behavior. It concludes that mastery of hypothesis formulation and application is essential for researchers and educators in supporting data-driven decision-making and is beneficial in improving the quality of learning.